Football, racism and peacebuilding in colonial Nigeria - Kelechi Johnmary Ani; Timothy Chibuike Anyanwu (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
The ubiquity of academic works on colonial Nigeria cannot be overemphasized. This has increased especially in the 21st Century such that there seems to be no area uncovered. But unfortunately, majority of these academic endeavors have been channeled to such areas as wars, resistances, imperialistic exploitations and so on. Little or no attention has been given to such areas as racism and leisure in colonial Nigeria. It then surfaces to argue that with the preponderant literature on colonialism, racism seemed to have only existed in such settlement colonies as South Africa, Kenya and so on. This research argues otherwise. Relying on oral interviews, archival materials, government gazettes, and relevant secondary data; the research employed historical and qualitative research approaches to fill this gap in scholarship. The work noted that racism punctuated the colonial regime in Nigeria, though not in the same extent with South Africa and other settlement colonies. The research further adds that the relationship between the colonizers and the colonized in Nigeria was not an all-time jigsaw nexus, as there were instances of recreational activities where the both parties participated alike. Soccer was such a recreational activity that eased the tensions of the time and also served as a peacebuilding measure between the opposing colonial rulers and the aboriginals. Filling the foregoing academic gaps is the major concern of this work, while recommending public and private partnership in promoting the culture of peace through football.